이동에이전트를 이용한 침입탐지 모델의 제안 - 황인선(In-Sun Hwang); 박경우(Kyung-Woo Park) (韓國컴퓨터情報學會論文誌, 2004)
The computer security is considered important due to the side effect generated from the expansion of computer network and rapid increase of the use of internet. Therefore, Intrusion detection system has been an active research area to reduce the risk from intruders. A number of advantages of using mobile agent computing paradigms have been Proposed. These advantages include : overcoming network latency, reducing network load, executing asynchronously and autonomously, adapting dynamically, and operating in heterogeneous environments. Many information security models have been proposed to mitigate agent-to-agent. agent-to-platform, and platform-to-agent element risks . In these paper, We have an object which is that through intrusion detection system development, the mobile agent is managed and through the analysis of performance data. the best environment is served. 컴퓨터네트워크의 확대와 인터넷 이용자의 증가에 따른 부작용으로 컴퓨터 보안 문제가 중요하게 대두되고 있다. 따라서 침입자들로부터 위험을 줄이기 위한 침입 탐지 시스템에 관한 연구가 활발하다. 이동에이전트를 이용하는 제안된 컴퓨팅 패러다임의 잇점은 네트워크의 지연시간 극복. 네트워크 부하 감소, 비동기적이고 자율적인 실행, 동적인 적합성과 이기종 환경에서의 운영이다. 많은 정보 보호 모델들은 agent-to-agent, agent-to-platform, 그리고 platform-to-agent 위험한 요소들을 완화하기 위하여 제안되었다. 본 논문에서는 침입 탐지 시스템의 개발을 통해서 이동 에이전트의 성능을 분석하여 관리함으로써 데이터가 최상의 환경을 유지하도록 하였다.